Neuropsychological approach in the investigation of time perception in late life depression - Mikeladze, L (KnE Life Sciences, 2018)
Late life depression is characterized by changes in time perception which are connected with the state of higher mental functions and their neuropsychological correlates. To the investigation of these connections our study was dedicated. A complex of methods included the Lurian neuropsychological diagnostics, prospective estimation of 5-, 10- and 15-second intervals and production of 1 min interval, retrospective estimation of the length of diagnostics and current time. Participants from control (n=26) and clinical (n=48) groups aged 50-81 were equal in sociodemographic characteristics. The interconnections between the characteristics of time perception and the different types of neuropsychological deficit as well as the characteristics of other higher mental functions were analyzed. With the purpose of the possibility of this multidimensional analysis the model of time perception was designed. The specifics of the inclusion and hierarchization of different components of the system with the purpose of achievement of adaptive result – time structuring of activity – was investigated. According to the hypotheses, in late life depression retrospective estimation deficit would be connected with memory deterioration, therefore, with dysfunction of deeper subcortical structures; the elaborated model of time perception was assumed to be useful in the analysis of time perception in its connection with other higher mental functions in old age. According to the results, in normal aging changes in time perception are connected with spatial deficit of memory, perception and praxis; in prospective judgments attention and control functions play a role. Time perception deficit is connected with dysfunction of deeper subcortical structures accenting in right hemisphere; prospective estimation – with prefrontal structures. In late life depression time perception deficit is connected with attention and control functions deficit; prospective judgments – with praxis; retrospective judgments – with memory deterioration. Prospective estimation deficit is connected with deficit in lefthemispheric structures and interhemispheric interaction; retrospective estimation deficit – with dysfunction of deeper subcortical structures. In different variants of aging tendencies to overestimation/underproduction of short intervals are connected with left-hemispheric dysfunction; to underestimation/overproduction – right-hemispheric dysfunction. Consequently, the hypotheses were approved and a full picture of interconnections between time perception and other functions and their neuropsychological correlates in late life depression was obtained. The proposed model of time perception was appropriate for analysis of time perception as it allows to reveal impaired the same as intact units of a functional system and to assume the primary or the secondary nature of impairments. The features of time perception interpreted based on the model may become the detectors of cognitive as well as affective dysfunction in old age. Keywords: time perception, neuropsychology, gerontology, gerontopsychology, late life, depression, late life depression, higher mental functions, functional system, model of time perception.